An SVM Method for Three-Phase Quasi-Switched Boost Inverter to Eliminate Leakage Current - Đỗ Đức Trí; Lê Hoàng Minh; Nguyễn Thanh Long; Trần Vĩnh Thanh (Journal of Technical Education Science, 2025)
Three-phase quasi-switched boost inverter (qSBI) have many advantages such as buck-boost operation and shoot-through (ST) immunity. However, conventional control methods for qSBI generate high common-mode voltage (CMV) and leakage current. This paper presents configuartion and control scheme for qSBI to eliminate leakage current of the inverter. Accordingly, the qSBI is modified by adding one inductor which is connected in series to the DC input source. In this topology, the CMV is the sum of CMV generated by inverter voltage vectors and the voltage of added boost inductor. The proposed scheme uses active vectors having the same CMV and ST vector to genertae output voltage. According to these vectors, the value of boost inductor is correspondingly selected to generate constant CMV. As a result, the leakage current of the inverter is eliminated. Simulation results with the help of PSIM software are used to verify the accuracy of the proposed method. Moreover, comparisons about quality of output voltage and the value of leakage current between the proposed method and conventional method are presented to figure out advantages/disadvantages of the proposed method.